Performance improvement of multi‐stage flash desalination with thermal vapor compression, a practical consideration. (3rd August 2021) - Assiri, Musa; Antar, Mohamed A.; Hamed, Osman; Lawal, Dahiru U.
Summary: This work focuses on reducing the energy needed to desalinate seawater through novel integration of MSF system with a thermal vapor compressor (TVC). The analysis extends to investigate positioning the TVC in different locations to find the most suitable location for TVC connection. Two different configurations of TVC's integration to MSF (single or double TVC's with MSF system) are proposed. Analytical models for brine recirculation MSF and MSF‐TVC have been established and validated against real plant data where a very good agreement was attained for important process parameters. Results show a significant improvement in thermal performance ratio (from 8.58 to 12.96) for the MSF‐TVC, while the steam consumption has also been reduced by 33%. Entrained vapor by TVC from a selected stage adversely affects the heat recovery of the recirculating brine, which drops the top brine temperature (TBT) by about 3°C. This resulted in a decrease in the productivity that is rectified by increasing the rate of brine recirculation to maintain the same desalinated water productivity. Energy analysis revealed a significant drop of about 34% in cooling seawater, which partly leads to energy saving of about 16%. Therefore, the proposed MSF‐TVC system shows higher thermal performance ratio, a decrease in the required heat transfer area, and reduction in the required energy per unit mass of pure water produced. Moreover, since the TVC requires higher motive steam pressure, this implies smaller steam pipe diameter. The effect on the integrated power plant load changes is also considered.